Baseball's all-time best hitters : how statistics can level the playing field - Schell, Michael J., 1957- (Princeton University Press, 1999)
Tony Gwynn is the greatest hitter in the history of baseball. That's the conclusion of this engaging and provocative analysis of baseball's all-time best hitters. Michael Schell challenges the traditional list of all-time hitters, which places Ty Cobb first, Gwynn 16th, and includes just 8 players whose prime came after 1960. Schell argues that the raw batting averages used as the list's basis should be adjusted to take into account that hitters played in different eras, with different rules, and in different ballparks. He makes those adjustments and produces a new list of the best 100 hitter.